2015
DOI: 10.11607/jomi.3532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insertion Method and Postinsertion Time Interval Prior to Force Application on the Removal Torque of Orthodontic Miniscrews

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Removal torque values after 180 days (Group 3) resulted almost the same as the initial torque and it would probably have shown a similar value after 4 weeks only. This interpretation is in contrast with that of Sharifi et al, in fact their study on removal torque in the first 6 weeks showed a reduced value, 29 a finding that is in accordance with previous literature 30,31 . A different analysis could be performed considering the surface type of minsicrews.…”
Section: Discussionsupporting
confidence: 46%
“…Removal torque values after 180 days (Group 3) resulted almost the same as the initial torque and it would probably have shown a similar value after 4 weeks only. This interpretation is in contrast with that of Sharifi et al, in fact their study on removal torque in the first 6 weeks showed a reduced value, 29 a finding that is in accordance with previous literature 30,31 . A different analysis could be performed considering the surface type of minsicrews.…”
Section: Discussionsupporting
confidence: 46%
“…Few investigations exist for prosthodontic implant removal [1,6,16,19] or miniscrew removal (e.g. [2,3,11,18,20]). All these scarce studies remain of little value for comparison, because their differences to the present investigation are too important to be ignored: different loading (prosthodontic vs. orthodontic), region of insertion, TAD dimensions in length, width and overall design, and surface characteristics differ significantly one from each other and disqualify any direct comparison.…”
Section: Discussionmentioning
confidence: 99%